Whole-genome analysis and description of an IMP-8-producing Ochrobactrum anthropi - Yanyan Zhang; Xuemei Yang; Ling Huang; Rong Zhang (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Obejectives: To explore the genomic characterization of an IMP-8-producing Ochrobactrum anthropic and give suggestions for the application of antibiotics. Methods: In 2021, the infection caused by CRKP was under control after nearly three months of using CAV, however, carbapenem-resistant O. anthropi isolates were collected from a rectal swab sample of a patient with Lumbar Disc Herniation Postoperative Infection. The rectal swab was then enriched in lysogeny broth overnight and inoculated onto China Blue agar plates containing 0.3µg/mL meropenem. And we investigated the characteristics of this carbapenem-resistant O. anthropi by MALDI-TOF MS, Immune colloidal gold technique, conjugation experiment, whole genome sequencing and antimicrobial susceptibility testing. Results: Antimicrobial susceptibility testing showed that the O. anthropi were resistant to imipenem, cefmetazole, ceftazidime, cefotaxime, piperacillin/tazobactam, sulbactam/cefopcrazone, ceftazidime/avibactam, cefepime, ciprofloxacin, aztreonam, and not susceptible to meropenem, ertapenem, polymyxin B, tigecycline, amikacin. Immune colloidal gold technique reflected that this strain produced IMP carbapenemases, and the presence of IMP-8 was verified by WGS, which was located in a 21,442 bp, nonconjugative plasmid. Conclusion: Improper antibiotic treatment can cause intestinal flora imbalance and even bacteremia in patients, we should use antibiotics wisely and develop individualized treatment options.